RESEARCH ON DYNAMIC PROPERTY FOR CASTING CRANE IN THE LOAD-LIFTING PROCESS BASE ON THERMO-ELASTIC COUPLING - HUANG Bin; FENG LiXia; XIANG ZaiYu (Jixie qiangdu)
As the rapid development of steel smelting industry,the casting cranes are developed tend to high speed and large-scale. The reliability and safety of a crane was largely affected by the dynamic property of the bridge. The 200/60t casting crane was studied to investigate the dynamic property of the bridge in the lifting process. In this scheme,the iron melt ladle lifting process dynamic model is established to analysis steel rope tension under different conditions. And then,the iron melt was taken as the heat source and taking heat radiation and conduction as heat transfer mode to analysis the temperature field of the bridge in the iron melt ladle lifting process. After that,loading the node temperature of the bridge model and applying structural load which is the sum of the steel wire rope tension and the weight of the main trolley,and the corresponding transient dynamic analysis is implemented by using thermo-elastic coupling method. Analysis results show that,the lifting position and speed of the iron melt ladle have great influence on the dynamic property of the steel wire rope. The temperature field of the bridge presents nonlinear variation with the iron melt ladle lifting,that the temperature field of the bridge changes more significantly while the lifting speed faster. It’s indicated that,the thermo-elastic coupling method can analysis the dynamic tress and property of bridge structure in the iron melt ladle lifting process more effectively. This study provides the theory basis for the structure reliability design of casting crane’s bridge.